Nonmalignant Pleural Effusions - Porcel, José M. (Seminars in Respiratory and Critical Care Medicine, 2022)
Although the potential causes of nonmalignant pleural effusions are many, the management of a few, including complicated pleural infections and refractory heart failure and hepatic hydrothoraces, can be challenging and requires the assistance of interventional pulmonologists. A pragmatic approach to complicated parapneumonic effusions or empyemas is the insertion of a small-bore chest tube (e.g., 14–16 Fr) through which fibrinolytics (e.g., urokinase and alteplase) and DNase are administered in combination. Therapeutic thoracenteses are usually reserved for small to moderate effusions that are expected to be completely aspirated at a single time, whereas video-assisted thoracic surgery should be considered after failure of intrapleural enzyme therapy. Refractory cardiac and liver-induced pleural effusions portend a poor prognosis. In cases of heart failure–related effusions, therapeutic thoracentesis is the first-line palliative therapy. However, if it is frequently needed, an indwelling pleural catheter (IPC) is recommended. In patients with hepatic hydrothorax, repeated therapeutic thoracenteses are commonly performed while a multidisciplinary decision on the most appropriate definitive management is taken. The percutaneous creation of a portosystemic shunt may be used as a bridge to liver transplantation or as a potential definitive therapy in nontransplant candidates. In general, an IPC should be avoided because of the high risk of complications, particularly infections, that may jeopardize candidacy for liver transplantation. Even so, in noncandidates for liver transplant or surgical correction of diaphragmatic defects, IPC is a therapeutic option as valid as serial thoracenteses.
Keywords: indwelling pleural catheter; therapeutic thoracentesis; pleurodesis; empyema; heart failure; hepatic hydrothorax; chest tube